The effects of training and competition on achievement goals, motivational responses, and performance in a golf-putting task - van de Pol, P. K.C.; Kavussanu, M.; Ring, C. (Journal of Sport & Exercise Psychology, 2012)
This study examined whether (a) training and competition influence achievement goals, effort, enjoyment, tension, and performance; (b) achievement goals mediate the effects of training and competition on effort, enjoyment, tension, and performance; and (c) the context influences the relationships between goals and effort, enjoyment, tension, and performance. Participants (32 males, 28 females; Mage = 19.12 years) performed a golf-putting task in a training condition and a competition condition and completed measures of goal involvement, effort, enjoyment, and tension; putting performance was also measured. Both task and ego involvement varied across training and competition, and variation in ego involvement explained variation in effort and enjoyment between these conditions. Ego involvement positively predicted effort in training and performance in competition, and interacted positively with task involvement to predict effort and enjoyment in competition. Our findings suggest that the distinction between training and competition is a valuable one when examining individuals` achievement motivation.